Carcass and edible non-carcass component yields in Menz and Horro ram lambs - Ermias, E.; Rege, J.E.O.; Anindo, D.O.; Amare, H.; Yami, A. (Ethiopian Society of Animal Production, 1998)
Slaughter data from 304 Menz and 153 Horro ram lambs were analyzed to determine between breed differences in yields of carcass and edible non-carcass components. Average age at slaughter was 515 days. Total edible non-carcass component yield (ENCC) was obtained as the sum of weights of blood, lungs (with trachea), liver with gall bladder), heart, kidneys, reticulo-rumen, omaso-abomasum, hind gut and abdominal and kidney fats. Total yield of usable products (TUP) was calculated as the sum of hot carcass weight (HCW) and ENCC. Slaughter weight (WS), HCW, ENCC and TUP were 24.7, 10.5, 4.3 and 14.8 kg, respectively, in Menz and 24.9, 10.4, 4.6 and 14.9 kg, respectively, in Horro. The difference between breeds in ENCC was statistically significant (p<0.01). Additionally, the Menz dressed higher (p<0.01) than the Horro (42 vs. 41 percent). This study emphasizes the need to pay attention to the total yield of usable products, rather than only to carcass weight and dressing percentages, in evaluating the suitability of various genotypes for meat production in cultures in which ENCC is traditionally consumed. Inclusion of this component in breed comparison may help understand farmer and consumer preferences for certain breeds.